Heat shock and hydrogen peroxide responses of Escherichia coli are not changed by dinucleoside tetraphosphate hydrolase overproduction. - Plateau, P (1987)
In Escherichia coli strains overproducing dinucleoside tetraphosphate hydrolase, the accumulation of dinucleoside tetraphosphates (AppppN, with N = A, C, G, or U) during heat shock or H2O2 treatment was reduced about 10-fold as compared with a control strain. This accumulation neither modified the pattern of the proteins induced by a temperature shift or H2O2 nor reduced the protection against oxidative damage induced by moderate H2O2 levels.